2005
DOI: 10.1097/01.sap.0000183802.38116.37
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Plate Removal in Maxillofacial Trauma

Abstract: This study reviewed the fate of titanium plates used to correct maxillofacial trauma in 76 patients to define risk factors for plate removal. Medical records of 76 consecutive patients at a single institution, over a 10-year period, were retrospectively reviewed. Variables included age, sex, trauma type, diagnosis, fracture type, fracture diagnosis, plate location, surgical approach, and reasons for plate removal. Fracture diagnosis was described as panfacial (42%), blowout (3%), midface (28%), zygoma (26%), m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
1
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 21 publications
1
56
1
4
Order By: Relevance
“…This was based on findings of a study from Canada which revealed that subjective (Nagase et al, 2005), and which mentioned the possible influence of the cold climate on this finding. The rate of patients undergoing PR for subjective reasons was notably lower in the present study (29.2%); however, it was clearly higher than the rates of 0% and 17.9% presented in studies conducted in Washington DC, USA (Murthy and Lehman, 2005) and Oman (Bakathir et al, 2008). We also observed that 14.6% of the patients who underwent PR stipulated that it was specifically because of cold intolerance, implying that the climate does have an influence on PR.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…This was based on findings of a study from Canada which revealed that subjective (Nagase et al, 2005), and which mentioned the possible influence of the cold climate on this finding. The rate of patients undergoing PR for subjective reasons was notably lower in the present study (29.2%); however, it was clearly higher than the rates of 0% and 17.9% presented in studies conducted in Washington DC, USA (Murthy and Lehman, 2005) and Oman (Bakathir et al, 2008). We also observed that 14.6% of the patients who underwent PR stipulated that it was specifically because of cold intolerance, implying that the climate does have an influence on PR.…”
Section: Discussioncontrasting
confidence: 77%
“…The great majority of the patients in the present study who had PR for unknown reason (81.3%) had plates removed from the mandible, possibly reflecting the surgeons' concern over future infection-related complications. Indeed, previous studies have shown that whenever osteosynthesis material needs to be removed from the mandible, the reason is most often related to infections (Islamoglu et al, 2002;Murthy and Lehman, 2005;Bakathir et al, 2008). In addition, as observed in the present study, the lower jaw is particularly susceptible to complications and to a subsequent need for PR.…”
Section: Pr Delaymentioning
confidence: 58%
See 2 more Smart Citations
“…14 Es motivo de controversia y criterio de cada cirujano craneomaxilofacial cuándo, cómo y bajo qué circunstancias se retira un sistema de fijación de osteosíntesis funcionalmente estable, con excepción de los casos en que la presencia de infecciones, sintomatología álgica, exposición intra y extraoral, malunión, pseudoartrosis y fractura de la placa e interferencia con el crecimiento facial, lo requieran. 15 El objetivo de este artículo es presentar el caso de un paciente con exposición de una placa de reconstrucción mandibular, postratamiento oncológico quien fue tratado de forma no convencional mediante el retiro del material de osteosíntesis y sin tratamiento posterior reconstructivo, mostrando adecuada función sin necesidad de otro tiempo quirúrgico, siendo un tratamiento diferente y un caso inusual en nuestro medio.…”
Section: Introductionunclassified